(untitled) (Research, Society and Development, 2022)
Introduction: It is of great importance to acknowledge the diagnostic criteria for the Polycystic Ovary Syndrome in adolescence, for an opportune diagnosis and appropriate therapeutic, preventing unnecessary treatment and lack of intervention. Objective: To investigate PCOS’s management in adolescents. Methods: Integrative revision based on 23 articles in English selected from the database: Pubmed/Medline and Cocharane, in the last 10 years. Clinical trials, meta-analyses, and systematic revisions were included, and those articles referring to PCOS in adult women, and those that weren’t about the treatment, were excluded. Results: The selected articles cover PCOS`s therapeutic in adolescents. For the clinical findings of hyperandrogenism and menstrual irregularity, combined oral contraceptives (COC) can be used as the first choice however, other antiandrogens are also effective, such as spironolactone. Besides, the association of topic therapy in the treatment of acne, along with physical methods such as depilation, for hirsutism, has shown good results. Regarding obesity, lifestyle change is the heart of the therapeutic but, drugs namely metformin, orlistat, and fluoxetine help to reduce body weight. Thus, for insulin resistance, metformin is the elected to intervene, having glitazones as a second choice. Conclusion: The treatment basis of PCOS in adolescents is lifestyle change. The use of metformin has shown a reduction of the Body Mass Index (BMI), associated with the lowering of blood glucose and improvements in the total cholesterol and LDL levels. The treatment with COCs resulted in modest cycle regulation, and reduction of acne and hirsutism, being cosmetics also used.